An approach for the reconstruction of a traditional masonry-wooden building located in an archeological area. Part II: Building reconstruction. Issue 2 (4th March 2022) - Akcay, Cemil; Korkmaz, Nail Mahir; Sayin, Baris
ABSTRACT: The study, which consists of a pair of articles, covers the reconstruction process of a traditional masonry-wooden mansion structure, which was built based on the Turkish house typology on the historical peninsula of Istanbul in the 1880s, and was then intentionally demolished in 1948. The paper, which constitutes the second part of the study, presents reconstruction operation in the location of the demolished building. In this context, the construction is carried out with a new approach in which the building load was transferred to the retaining system in order to protect the cultural layer in the construction area. In the reconstruction, steel frame system is preferred instead of the original wooden construction system and material. In contrast, the construction gauge and plan scheme of the original building was taken as a basis in reconstruction. It is concluded that the presented approach is suitable as a new construction technique considering the parameters such as seismic effect, archeological ruins, building–environment relationships and needs analysis in reconstruction of the demolished historical buildings.